Cholelithiasis and cholecystitis in children and adolescents: does this increasing diagnosis require a common guideline for pediatricians and pediatric surgeons? - Diez, Sonja; Müller, Hanna; Weiß, Christel; Schellerer, Vera; Besendörfer, Manuel (BMC gastroenterology, 2021)
In contrast to adults, for whom guidelines on the cholelithiasis treatment exist, there is no consistent treatment of pediatric patients with cholelithiasis throughout national and international departments, most probably due to the lack of evidence-based studies.
Gesehen am 12.07.2021